Cybersecurity in Cloud Systems: Opportunities, Challenges, and Way Forward - Sabitha Banu A; Yasir Khan; Mariyum Munir; Mehdi Gheisari; Sara Abou Chakra (Cloud Computing and Data Science, 2025)
Cloud computing has become an essential requirement for enterprises, providing flexibility and scalability. According to a 2023 Gartner report, over 85% of organizations will embrace a cloud-first principle by 2025. Leading companies like Netflix, Amazon, and Dropbox rely heavily on cloud infrastructure to manage massive volumes of data, support global user access, and scale services dynamically based on demand. This shift to cloud-based solutions enables businesses to reduce operational costs, enhance agility, and accelerate innovation. Since organizations are increasingly opting for cloud services, this introduces a significant number of cybersecurity challenges, including risks to data confidentiality, integrity, and availability. Moreover, these threat actors have found sophisticated ways of exploiting vulnerabilities in cloud platforms and environments, leading to unauthorized access, data loss, and financial gains. This paper offers a comprehensive analysis of the current situation of cybersecurity in a cloud environment, focusing on the critical vulnerabilities that arise from shared infrastructure and multi-tenancy. We identify key security risks and propose enhanced security frameworks specifically designed for cloud environments. Our findings show the need for more efficient security measures and continuous supervision to protect important information in the cloud. Furthermore, we underscore key cybersecurity challenges that security teams confront while integrating security protocols in cloud systems. Lastly, the paper concludes the review by bringing to light certain areas that can be focused on in the future for deeper understanding and new explorations.